ANALISIS MUSIK BAWAKNG DAYAK KANAYATN DI PAHAUMAN KALIMANTAN BARAT - Kurniawan, Andri; Syahrani, Agus; Silaban, Chiristianly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research based on the researcher interest to Dayak Kanayatn Bawakng music and the perseption that so many Dayak Kanayatn people didn’t know about 7 kind of Bawakng music. The purpose of this research are: 1) to analyze the musical text which are the form and the music element of Dayak Kanayatn Bawakng Music, 2) to analyze musical context in the form of function and value of Dayak Kanayatn Bawakng music. The method that used in this research is descriptive qualitative and used musicology and anthropology approach. Data that contained in this research is the result of interview to the interviewer who mastered Dayak Kanayatn Bawakng music. Data were analyzed qualitatively, with Ferdinan, S.Sn (Dayak Kanayatn music observer), Drs. Kesimen (culture observer), Yupiter Bujakng Pabaras (traditional musician) and some people who active and know about Dayak Kanayatn Bawakng music. Based on the data analysis we can conclude that Dayak Kanayatn Bawakng music is the shortest music pattern among the other Dayak musics in Kalimantan Barat (maybe in all region of Kalimantan). This music is Pentatonic Unhemietonic scale (music without half range note). Bawakng music has a unique syncopation pattern (berumbal/betingka) that refers to one main motive pattern in Dau We’.  Keywords: Analyze, Bawakng music, Dayak Kanayatn, West Borneo.